2011
DOI: 10.1111/j.1349-7006.2011.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of CD10+ myeloid cells in association with tumor budding at the invasion front of colorectal cancer

Abstract: The expression of CD10 in tumor cells has been reported to correlate with liver metastasis in colorectal cancer (CRC). However, fibroblasts and immune cells positive for CD10 at the tumor invasion front have not been comprehensively studied. We classified CD10 expression patterns into three types of cells, tumor cells (tCD10), stromal myofibroblasts (sCD10), and immune cells (iCD10), and investigated their correlation with the expression of transforming growth factor-b (TGF-b1) protein and tumor budding grade.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
7
34
1
Order By: Relevance
“…14 Additionally, CD10 expression was observed in tumor-infiltrating granulocytes and was correlated with worse survival. 15 In prostate carcinoma, tumoral CD10 expression was used to identify subsets of patients with poor prognoses for survival, higher risk of lymph node metastases, and higher Gleason grades. 16,17 By contrast, in hematopoietic tumors such as malignant lymphoma, tumoral CD10 expression was correlated with better survival.…”
Section: Discussionmentioning
confidence: 99%
“…14 Additionally, CD10 expression was observed in tumor-infiltrating granulocytes and was correlated with worse survival. 15 In prostate carcinoma, tumoral CD10 expression was used to identify subsets of patients with poor prognoses for survival, higher risk of lymph node metastases, and higher Gleason grades. 16,17 By contrast, in hematopoietic tumors such as malignant lymphoma, tumoral CD10 expression was correlated with better survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TGF-␤ is an important cytokine involved in the crosstalk between tumor cells and stroma cells [2,59]. The infiltration of CD10 + myeloid cells at the invasion front interact with TGF-␤ and enhance the tumor-budding grade [167]. Selective and transient loss of the basement membrane (BM) at the invasive front is correlated with increased distant metastasis and poor patient survival in CRC.…”
Section: Emt and Rumor Buddingmentioning
confidence: 99%
“…1 over the last decade, multiple studies have focused on CD10 as a potential marker for high-risk colorectal cancer. [1][2][3][4][5][6][7][8][9][10][11][12] CD10, a cell membrane metallopeptidase, was initially used in the diagnosis of acute lymphocytic leukemia; studies in the last decade, mostly from Japan, have repeatedly shown CD10 to be linked to colorectal cancer as well. 2 early work has demonstrated that CD10 expression is integral to colorectal cancer progression and invasion, [3][4][5] whereas more recent studies have shown CD10 presence as a significant predictor of liver metastasis.…”
mentioning
confidence: 99%